Evaluation of serum samples in long cryopreservation for SomaScan proteomics and sex differences in elderly Japanese adults - Ruriha Beppo; Yuki Ohashi; Ken Yamamoto; Fumie Kinoshita; Tomoko S. Kato; Masahisa Katsuno; Tatsuaki Matsubara; Mitsuhiro Yokota; Sahoko Ichihara; Masahiro Nakatochi (Scientific Reports)
Abstract Many biobanks store biological samples and use them for various analyses, including proteomics. Therefore, it is necessary to consider the denaturation of target proteins during long-term storage. We analyzed 16-year-old cryopreserved serum samples using the SomaScan platform, a novel proteomic assay, to determine whether adiponectin and resistin concentrations were consistent with those measured in our previous studies using a different platform. The results suggested that long-term cryopreserved serum samples could be used for future studies of at least adiponectin and resistin, which are closely related to the pathophysiology of diabetes, cardiovascular disease, and other metabolic diseases. Therefore, 7,289 SomaScan-assayed circulating proteins were compared between 20 men and 20 women aged ≥ 50 to determine sex differences. In total, 20 serum proteins showed significant sex differences. Of these, proteins that showed a more than two-fold difference in concentration between sexes contained heterodimeric forms of gonadotropic proteins such as CGA|FSHB, CGA|CGB3|CGB7, and CGA|LHB, which are the biologically active forms of these hormones. The present study is the first to report the possibility of using long-term cryopreserved serum samples for the SomaScan assay, and the results show that the SomaScan assay may be useful for analyzing sex differences focusing on gonadotropic hormones.